Structure/property (constitutive and spallation response) of additively manufactured 316L stainless steel. (1st October 2017) - Gray, G.T.; Livescu, V.; Rigg, P.A.; Trujillo, C.P.; Cady, C.M.; Chen, S.R.; Carpenter, J.S.; Lienert, T.J.; Fensin, S.J.
Abstract: For additive manufacturing (AM) of metallic materials, the certification and qualification paradigm needs to evolve as there is currently no broadly accepted "ASTM- or DIN-type" additive manufacturing certification process or AM-produced material specifications. Accordingly, design, manufacture, and subsequent implementation and insertion of AM materials to meet engineering applications requires detailed quantification of the constitutive (strength and damage) properties of these evolving materials, across the spectrum of metallic AM methods, in comparison/contrast to conventionally-manufactured metals and alloys. For this study, cylindrical samples of 316L SS were produced using a LENS MR-7 laser additive manufacturing system from Optomec (Albuquerque, NM) equipped with a 1 kW Yb-fiber laser. The microstructure of the AM-316L SS was characterized in both the "as-built" AM state and following a heat-treatment designed to obtain full recrystallization to facilitate comparison with annealed wrought 316L SS. The constitutive behavior as a function of strain rate and temperature was characterized and is compared to that of annealed wrought 316L SS plate material. The dynamic shock-loading-induced damage evolution and failure response of all three 316L SS materials was quantified using flyer-plate impact driven spallation experiments at peak stresses of 4.7 and 6.5 GPa. The spall strength of AM-produced 316L SS and the recrystallized-AM-316L SS were found to decrease with increasing peak shock stress while the annealed wrought 316L SS spall strength remained essentially constant. The damage evolution, characterized using optical metallography and electron-backscatter diffraction (EBSD), was found to vary significantly across the three 316L SS microstructures while the three samples loaded to a peak shock stress of 6.5 GPa displayed only ∼12% differences in spall strength. Graphical abstract: Image 1